The Implementation of Digital Multilingual Thematic Dictionary towards The Fourth Grade Students’ Literacy Skill: An Experimental Study - Luh Siantari; Ni Made Ratminingsih; I Gede Budasi (Institut Agama Islam Negeri Palopo, 2023)
The study aims to investigate whether there is a significant impact on utilizing a digital multilingual dictionary for fourth grade students’ literacy skills. The method of this study is a quasi-experimental and quantitative research approach. The samples were taken using statistical matching techniques by Fraenkel et al., (2012). The samples are the fourth grade students of SDN 2 Pacung as the control group and SDN 1 Banjar as the experimental group. The two groups received three treatments with three themes including: Greeting & Introduction, Family, and Things in the Classroom. The instrument of this study was a students’ literacy test which consisted of a pre-test, treatment, and post-test. To analyze the data quantitatively, researchers used descriptive statistical analysis, inferential statistics, and the N-Gain score test. The results from the N-Gain score of the controlled group were 50.5% and 62,71% for the experimental group. It revealed that the use of a digital multilingual thematic dictionary was categorized as moderately effective compared to the printed version in improving fourth grade students’ literacy skills compared to the controlled group who were treated by the printed version. Therefore, the digital multilingual thematic dictionary significantly affects fourth grade students’ literacy skills.